A putative membrane-associated YdjB-like protein from Salmonella enterica exhibits a non-canonical ACT-like fold - Ju Hyeong Kim; Yong Jun Kang; Young Woo Kang; So Eun Park; Hyo Been Jin; Eunmi Hong; Hyun Ho Park (PLoS ONE, 2025)
The Aspartokinase-Chorismate mutase-TyrA (ACT) domain is a conserved regulatory module found in a wide range of proteins involved in diverse biological processes, including amino acid metabolism, signal transduction, and cytoskeletal organization. Despite extensive studies, the structural and functional diversity of ACT domains continues to expand. Here, we present the high-resolution crystal structure of an 18 kDa YdjB-like protein from Salmonella enterica (seYdjB-like protein), a conserved but previously uncharacterized ACT domain-containing protein. Structural analysis reveals a novel ACT-like fold distinct from canonical ACT domains, despite superficial resemblance to aspartokinase. Interestingly, seYdjB-like protein forms a stable dimer in solution and is predicted to be associated with the membrane, suggesting functional divergence from typical cytosolic ACT domain proteins. This structure represents an alternative form of the ACT domain, expanding our understanding of ACT domain architecture and its functional potential. Given its conservation across bacterial species such as E. coli and S. enterica, this putative membrane-associated ACT-like protein may play an important but previously unrecognized role in bacterial physiology. Our results identify this 18 kDa ACT-like domain containing YdjB-like protein as a unique dimeric membrane protein featuring a non-canonical ACT-like fold.